BIOMARKER POTENTIAL OF IQ-DOMAIN GTPASE-ACTIVATING PROTEINS FAMILY PROTEIN IN PANCREATIC CANCER: A MINI REVIEW - Sumarpo, Anton; Sahamastuti, Agnes Anania Triavika; Tjugianto, Gisella Edny; Yonathan, Kenny; Agustriawan, David (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: Our present study was done to understand molecular regulatory mechanisms of IQGAP proteins and their potentials as biomarker in pancreatic cancer. Methods: In this review, relevant studies were obtained by assessing the PubMed database using the combination of words that included IQGAPâ€ and pancreatic cancerâ€. Results: There is an increasing evidence showing that the expression of IQGAP1 and IQGAP3 is positively correlated with tumorigenesis; however, IQGAP2 might play a role to suppress tumor progression. Conclusion: IQGAP proteins might have potentials as predictive and prognostic biomarker for human pancreatic cancer.